Studi Pengelolaan Limbah B3 di RSUD dr Drajat Prawiranegara Kabupaten Serang - Ade Ariesmayana; Hajali . (Jurnal Serambi Engineering, 2018)
The purpose of this study was to describe the B3 waste management system in the District General Hospital dr. Drajat Prawiranegara Serang District 2016, identifying the sources and characteristics of B3 waste in their respective sources of waste in the District General Hospital dr. Drajat Prawiranegara Serang District with existing standards. This study uses observation.  collecting datausing systematic observation techniques, while in-depth analysis of the data processed by qualitative techniques to describe the efforts pengelolahan hazardous wastes and toxic B3 at Regional GeneralHospital dr. Drajat Prawiranegara Serang District were then compared with BAPEDAL regulation No. 01/05 / 1995. The results showed the Regional General Hospital dr, Serang regency degrees Prawiranegara produce volumes of hazardous and toxic waste. Efforts management of hazardouswastes and toxic B3 of the lug or packaging, storage, transportation done well.